2017
DOI: 10.18311/jhsr/2017/18056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ophthalmic Plastic Procedures in a Tertiary Centre

Abstract: Orbito-oculoplastics diseases and deformities tend to impact negatively on the psycho-social, economic as well as the educational achievement of affected persons. Ophthalmic plastic procedures are performed to improve the appearance and function of the eyelids and face of the affected person. Purpose: To determine the prevalence and indications of oculoplastic procedures in oculopastic subspecialty in order to provide data base for management of ophthalmic plastic conditions in our centre. Method: The clinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…These results are similar to those reported by Omotoye et al [2]. Several studies [1][2][3] have found that Oculoplastic diseases were more common than orbital diseases and the findings of this study suggest the same with 80.7% of the cases being oculoplastic. It is of importance to note that overall, 54% of patients included in the study were under the age of 40 years.…”
Section: Demographicssupporting
confidence: 92%
“…These results are similar to those reported by Omotoye et al [2]. Several studies [1][2][3] have found that Oculoplastic diseases were more common than orbital diseases and the findings of this study suggest the same with 80.7% of the cases being oculoplastic. It is of importance to note that overall, 54% of patients included in the study were under the age of 40 years.…”
Section: Demographicssupporting
confidence: 92%
“…The eye lid disorders seen in the oculoplastic subspecialty clinic of ophthalmology department of the tertiary institution was 8.3% of all new cases in this centre with male preponderance. An earlier study of analysis of ophthalmic plastic procedure in the same centre 7 showed a lower incidence which may be due to the fact that only cases that needed surgical procedures were included in the study. All other studies were silent on the incidence of eyelid disorders in their work 1,2,6,8 .…”
Section: Discussionmentioning
confidence: 97%